Potensi Serat Pelepah Nipah Sebagai Bahan Baku Binderless Fiberboard - Kristiningsih, Ari; Wittriansyah, Khoeruddin; Ariawan, Radhi (P3M Politeknik Negeri Cilacap, 2025)
Fiberboard uses a lot of agro-industry waste materials combined with synthetic adhesives containing formaldehyde. The weakness of this adhesive is that it can cause health problems such as cancer and eye irritation. Lignin has properties and content similar to formaldehyde. Nipah has lignin and cellulose content that can be developed into binderless fiberboard. The purpose of this study was to analyze the potential of Nipah frond fiber to make a binderless fiberboard. The characteristics of fiberboard that will be explored include density and water content. Nipah frond binderless fiberboard is made using a press machine with a pressure of 50 bar, and a temperature of 100oC for 20 minutes. The density between 0.46-0.52 which is by the requirements of SNI 03-2105-2006 and the water content of 5.98% - 7.70% is also by the requirements of JIS 5908: 2003 and SNI 03-2105-2006. Based on these results, it can be concluded that Nipah fronds can be used as raw material for binderless fiberboard.